2001
DOI: 10.1071/bt00013
|View full text |Cite
|
Sign up to set email alerts
|

Community-wide germination strategies in a temperate rainforest of Southern Chile: ecological and evolutionary correlates

Abstract: Delayed seed germination (‘dispersal in time’), as a component of a plant’s germination strategy, was studied in dicotyledoneous species of a temperate rainforest flora in Chiloé Island (42°30′S), southern Chile. The objective of this investigation was to assess, for this temperate rainforest flora, what proportion of interspecific variation in the time of seed germination—measured in days since the onset of seed dispersal in space—could be attributed to the plants’ historical and phylogenetic background and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 56 publications
3
46
0
2
Order By: Relevance
“…This result is in accord with the former studies. For example, Seven species of Alstroemeria that grow in different mountain and lowland habitats in South America exhibited similar germination strategies, regardless of their habitat of origin (see Figueroa and Armesto 2001); Baskin et al (1993) reported analogous results when dormancy types were compared among species in the family Asteraceae; Species belonging to the Arcto-Tertiary flora presently inhabiting deciduous North American forest, had germination strategies that matched those of congeneric species presently occurring in East Asia (Baskin and Baskin 1998).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This result is in accord with the former studies. For example, Seven species of Alstroemeria that grow in different mountain and lowland habitats in South America exhibited similar germination strategies, regardless of their habitat of origin (see Figueroa and Armesto 2001); Baskin et al (1993) reported analogous results when dormancy types were compared among species in the family Asteraceae; Species belonging to the Arcto-Tertiary flora presently inhabiting deciduous North American forest, had germination strategies that matched those of congeneric species presently occurring in East Asia (Baskin and Baskin 1998).…”
Section: Discussionmentioning
confidence: 66%
“…For example, phylogenetic closeness explained much interspecific variation in breeding systems, seed mass, flowering phonologies, fleshy-fruit traits and reproductive syndromes in Mediterranean, tropical and temperate floras (see Figueroa and Armesto 2001). For example, seed germination rates of species belonging to the same plant families in Sheffield, England, were more similar than those of species in different families (Grime et al 1981); Figueroa and Armesto confirmed that phylogenetic relationships significantly influenced GT (mean time of seed germination in days from sowing) for species in the forest flora of Chiloé ; The phylogenetic pattern of seed mass was also previously shown in different floras (Mazer 1990;Lord et al 1995).…”
Section: Mean Wgimentioning
confidence: 99%
“…Comparative surveys have shown that germination behavior is also related to other life history traits such as seed mass (Mazer 1989;Shipley and Parent 1991;Jurado and Westoby 1992;Guo et al 2000;Pearson et al 2002;Bu et al 2007), seed dispersal (Willson and Traveset 2000) and life form (Gross 1984;Figueroa 2003). In addition, some of the variance in life history traits between species is associated with phylogeny (Mazer 1989(Mazer , 1990Leishman et al 1995;Figueroa and Armesto 2001;Figueroa 2003;Zhang et al 2004;Simons and Johnston 2006;Bu et al 2007), and this association is often attributed to phylogenetic constraints (Kochmer and Handel 1986). Therefore, to assess the role of natural selection on seed germination at the community level, we should take into account as many variables as possible when measuring the effect of any single variable.…”
Section: Introductionmentioning
confidence: 98%
“…The germination index (GI) is based on number of seeds that germinated and the germination rate. These parameters were also calculated from the formulas proposed by (Figueroa and Armesto, 2001;Bu et al, 2007;Wu and Du 2007).…”
Section: Seed Germination Testmentioning
confidence: 99%